2017
DOI: 10.1111/rda.13036
|View full text |Cite
|
Sign up to set email alerts
|

Single layer centrifugation of fresh dromedary camel semen improves sperm quality and in vitro fertilization capacity compared with simple sperm washing

Abstract: Single layer centrifugation (SLC) through a colloid is a tool for selecting viable mammalian spermatozoa but has not been used previously for fresh dromedary camel sperm. Semen from six camels (2 ejaculates/male) was diluted 1:5 (v:v) or 1:10 (v:v) in a Tris-citrate-fructose buffer for mechanical liquefaction by gentle pipetting. Following liquefaction, semen was processed either by SLC or by centrifugation without a colloid (control). Total and progressive motilities, CASA kinematics, vitality and acrosome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Finally, single layer centrifugation has been used in different species as a step prior to other biotechnologies such as IVF (Björnsdotter Sjunnesson, Morrell, & González, 2013; Malo et al., 2018; Malo, Crichton, Morrell, Pukazhenthi, & Skidmore, 2017; Martinez‐Alborcia et al., 2013). As far as SAC are concerned, some authors have also reported the use of the colloid Percoll ® as part of the sample preparation for embryo production (Berland et al., 2011; Conde et al., 2008; Condori et al., 2010; Huanca et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, single layer centrifugation has been used in different species as a step prior to other biotechnologies such as IVF (Björnsdotter Sjunnesson, Morrell, & González, 2013; Malo et al., 2018; Malo, Crichton, Morrell, Pukazhenthi, & Skidmore, 2017; Martinez‐Alborcia et al., 2013). As far as SAC are concerned, some authors have also reported the use of the colloid Percoll ® as part of the sample preparation for embryo production (Berland et al., 2011; Conde et al., 2008; Condori et al., 2010; Huanca et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have been carried out in this direction. It was found that SLC positively influenced some of the semen parameters in species and breeds such as great panda (Cai et al, 2018), brown bear (Álvarez‐Rodríguez et al, 2016; Anel‐Lopez et al, 2017), camel (Malo, Crichton, Morrell, Pukazhenthi, & Skidmore, 2017), misty panther (Tipkantha et al, 2016), andalusian donkey (Ortiz et al, 2015), red deer (Anel‐López et al, 2015) or blanca‐celtibérica goat (Jiménez‐Rabadán et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Needling and pipetting, i.e., repeated aspiration of semen through a needle or a pipette, respectively, may help liquefaction but sperm quality tends to be reduced, possibly due to physical damage or by release of reactive oxygen species that may subsequently affect sperm membranes and chromatin. Prior extension of the semen sample with a buffered semen extender, followed by gentle pipetting during incubation, was shown to liquefy semen from dromedary camels (34). Removal of the freed spermatozoa from the seminal plasma is needed as the gel tends to reappear with time, trapping the spermatozoa once more.…”
Section: Semen Handlingmentioning
confidence: 99%
“…A comparison of swim-up and colloid centrifugation of llama spermatozoa (after treatment of the ejaculate with collagenase) concluded that colloid centrifugation was the method of choice for preparing spermatozoa (39). In studies on dromedary camel semen that had been subjected to gentle pipetting, i.e., without enzyme treatment, Malo et al (34) showed that sperm quality parameters and in vitro fertilization ability of spermatozoa were improved by SLC compared with simple sperm washing. The colloid separated live motile spermatozoa from seminal plasma, dead cells, debris, and extender.…”
Section: Semen Handlingmentioning
confidence: 99%
See 1 more Smart Citation